471 - Online program to cope to prolonged grief: an end-user centered approach. (October 2020) - Isaac, J.; Gouveia, A.; Suarez-Gomez, M.; Rodrigues, A.; Sousa, R.; Canhão, H.; Ferreira, L.; Alcobia, C.; Pinho, R.; Cabrita, M.; van Velsen, L.; Matos-Pires, A.
Abstract : Background: Loss of a spouse is a frequent occurrence in later life, with about 10% of the individuals finding themselves unable to cope and progressing to prolonged grief, risking further mental and physical problems. Objective: The development and implementation of an online grief program, such as LEAVES ( optimizing the menta L hEalth and resilience of older Adults that haVe lost th Eir spou Se via blended, online therapy ), intends to improve prevention and treatment of prolonged grief, so that elderly mourners can continue to lead an active, meaningful and dignified life. Methods: The LEAVES program, a project under AAL (Active and Assisted Living) 2019 Call for Sustainable Smart Solutions for Ageing Well, is in development by an international consortium and integrates academical, clinical and technical experts. The project will take place between February 2020 and January 2023 and involve real-life evaluation of 315 end-users. The Psychiatric Department at the Health Unit of Baixo Alentejo (ULSBA) will offer the service to its primary users, blending online services with telephone, video calls and face-to-face sessions. Widowed older adults >65 that express the need for help in mourning their spouse will be recruited in the community as well as via the geriatric psychiatry team and primary care. Results: With LEAVES program we aim for older adults to process the loss of a spouse in a blended online/presential environment, detecting olders at risk for complications, reveal negative trends in their emotional life, and act to counter such trends. The evaluation will focus on wellbeing and involve several measures to assess grief symptoms, loneliness, hopelessness, satisfaction and quality of life. Conclusions: ULSBA will use LEAVES to improve clinical practice on preventing and managing prolonged grief as well as, after testing and validating it in this project, to save economical costs and improve effectiveness, both to hospital and patients.